2020
DOI: 10.31373/ejtcm/115402
|View full text |Cite
|
Sign up to set email alerts
|

Acute cholecystitis in patients with diabetes mellitus - systematic review

Abstract: Introduction: According to the WHO, an estimated 422 million people are suffering from diabetes worldwide. Among them, the incidence of cholelithiasis is higher than in the healthy population. The aim of this literature review was to summarize the available evidence about acute cholecystitis in patients with diabetes. Materials and methods: This study adhered to the PRISMA guidelines. The course of hospitalization of patients with and without diabetes who underwent cholecystectomy due to acute cholecystitis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Similar studies on outcomes of cholecystectomy in diabetic patients have confirmed the interdependency between DM and acute coronary syndromes (11,23). Moreover, other systemic complications have been revealed to be associated with DM including respiratory, renal decompensation, sepsis, and systemic infections (11,12,15,17). In the present study, there were no pulmonary and renal complications, and the hospital-acquired infection rates did not differ between the 2 study groups.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar studies on outcomes of cholecystectomy in diabetic patients have confirmed the interdependency between DM and acute coronary syndromes (11,23). Moreover, other systemic complications have been revealed to be associated with DM including respiratory, renal decompensation, sepsis, and systemic infections (11,12,15,17). In the present study, there were no pulmonary and renal complications, and the hospital-acquired infection rates did not differ between the 2 study groups.…”
Section: Discussionsupporting
confidence: 86%
“…Ischemic heart disease has been revealed to be significantly associated with DM due to the occurrence of both large vessels (accelerated atherosclerosis) and microvascular disorders. Similar studies on outcomes of cholecystectomy in diabetic patients have confirmed the interdependency between DM and acute coronary syndromes (11,23). Moreover, other systemic complications have been revealed to be associated with DM including respiratory, renal decompensation, sepsis, and systemic infections (11,12,15,17).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Costs of emergency surgery in diabetic patients are significantly higher (p = 0.015) than in non-diabetic. This is due to increased levels of complications intraoperatively and in postoperative period in diabetic patients with acute cholecystitis in comparison to-non diabetics [11,19,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its many complications, diabetes mellitus is associated with significant costs in public healthcare systems around the globe [2,3]. Acute cholecystitis in diabetic patients is often complicated by gangrenous cholecystitis [1], peritonitis, preoperative perforation, impaired wound healing, infections, increased risk of cardiovascular events and renal failure [4][5][6][7][8][9][10][11]. For this reason, diabetic patients hospitalisation costs are estimated to be higher than non-diabetic.…”
Section: Introductionmentioning
confidence: 99%